The potential for dispersant use as a maritime oil spill response measure in German waters. Issue 2 (April 2018) - Grote, Matthias; van Bernem, Carlo; Böhme, Birgit; Callies, Ulrich; Calvez, Ivan; Christie, Bernard; Colcomb, Kevin; Damian, Hans-Peter; Farke, Hubert; Gräbsch, Carolin; Hunt, Alex; Höfer, Thomas; et al.
Abstract: In case of an oil spill, dispersant application represents a response option, which enhances the natural dispersion of oil and thus reduces coating of seabirds and coastal areas. However, as oil is transferred to the water phase, a trade-off of potential harmful effects shifted to other compartments must be performed. This paper summarizes the results of a workshop on the current knowledge on risks and benefits of the use of dispersants with respect to specific conditions encountered at the German sea areas. The German North Sea coast is a sensitive ecosystem characterised by tidal flats, barrier islands and salt marshes. Many prerequisites for a potential integration of dispersants as spill response option are available in Germany, including sensitivity maps and tools for drift modelling of dispersed and undispersed oil. However, open scientific questions remain concerning the persistence of dispersed oil trapped in the sediments and potential health effects. Highlights: Overview on current practice, guidance on and operational experience concerning dispersant use Relevant aspects for spill response planning in German marine waters (geography, ecosystems, meteorology, hydrodynamics etc.) Discussion of specific risks and benefits of potential dispersant uses in Germany and identification of open questions